Evaluation of extraction solvent on antioxidant activity, total phenolic and total flavonoid content in elaeis guineensis / Wan Zuraida Wan Mohd Zain, Siti Nur Lisha Mohd Ghazali and Samsiah Jusoh - Wan Mohd Zain, Wan Zuraida; Mohd Ghazali, Siti Nur Lisha; Jusoh, Samsiah (Universiti Teknologi MARA Cawangan Pulau Pinang, 2019)
Oil palm or Elaeis guineens is a rich natural source of phenolic with flavonoid as the main constituents. These phenolics are potent antioxidants that can be used in the food industry, cosmetics and others. Therefore, the study was aimed to determine the effect of solvents which were methanol, ethyl acetate and hexane also different plant parts which were leaves, frond and fresh fruit bunch toward antioxidant activity (AOA), total phenolic content (TPC) and total flavonoid content (TFC). The antioxidant was analysed using the DPPH method, TPC by Ciocalteu assay and TFC by aluminium chloride colorimetric assay. The result from ANOVA indicated that there was a difference (P < 0.05) in the extracting ability of each solvent and different plant parts for AOA, TPC and TFC. Generally, the result suggested that methanol give the highest antioxidant activity, TPC and TFC compared to ethyl acetate and hexane. Therefore, the solvent used should be selected properly to allow for a high level of extraction efficiency.